Determinating The Value of Capital Expenditure Allocation in Indonesia Local GovernmentDeterminating The Value of Capital Expenditure Allocation in Indonesia Local Government - Mahameru Rosy Rochmatullah; Rudy Hartanto; Atwal Arifin (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2016)
Capital expenditure allocation is aimed to preservation and expansion of local government fixed assets that provide long-term benefit. This paper investigates the factors that affect the capital expenditure allocation in Indonesian local government. Employing a panel pooled data-regression (fixed effect), our results reveal that local productivity, local funding, local budget requirement, and local establishment status are related to the value of capital expenditure. This research found that efficiency of capital expenditure management is related with fiscal dependence.